Exploring natural plant fiber choices and treatment methods for contemporary composites: A comprehensive review - Muthuselvan Balasubramanian; R. Saravanan; Sathish T (Results in Engineering)
The growing importance of composite materials in engineering is reshaping industries such as automotive, maritime, sports, and aerospace. As industries seek sustainable alternatives to synthetic fibers, natural fibers have emerged as a promising solution due to their abundance, low cost, and biodegradability. Natural fibers not only address environmental concerns but also offer a competitive strength-to-weight ratio, making them an attractive choice for reinforcement in modern composites. They overcome many of the limitations of synthetic fibers and fiberglass, offering enhanced mechanical, thermal, and physical properties while being easier to manufacture. This comprehensive review delves into the latest advancements in natural fiber composites, exploring newly discovered fibers and innovative treatment methods. By examining these natural fiber-based polymers, the review highlights their potential to meet the ever-evolving demands for materials that combine superior performance with affordability and sustainability.